Pharmacological potential of Sargassum sp. of west coast of Maharashtra Kunkeshwar, India - Abdi, Gholamreza; Karande, Vanita Chandrashekhar; Mohammed, Arifullah; Abbasi Tarighat, Maryam; Wen Goh, Khang; Abdul Kari, Zulhisyam; Seong Wei, Lee; Ahmad Mohd Zain, Muhammad Rajaei; Mohammadi, Mehdi; Ee Lee, Gaik; Barwant, Mukul M. (Frontiers in Marine Science, 2022)
Seaweed is one promising plant group of among of all. In this investigation we have discussed about Nutraceutical potential and Pharmacology value of Brown algae (Sargassum sp). Nutraceutical indicates that the nutritive and Pharmacological potential. We have collected the plant material from western coast in Maharashtra's Sindhudurg district at kunkeeshwar. We have focused on the Physicochemical property of Sargassum sp that results revealed that water-soluble extractive value (15 ± 0.28), alcohol soluble extractive value (1.5 ±0.030), moisture content (1.33 ±0.038), total cash value (41 ±0.67) while acid insoluble (0.026 ±0.00) all are expressed in (%). Their nutritive profile is also expressed by GCMS results presented that the chromatogram of aqueous extract of Sargassum sp there are total 25 compounds detected all this compound can be observed in chromatogram structure of all compound are shown, Out of that highest retation time and relative areas is n-hexadanoic -acid after that 1-Hexyl-2-nitrocyclohexaneafter that Ocladecanoic acid has been detected also observed Pharmacological activity namely Antioxidant activity by DPPH assay explain that activity is dependent on concentration . maximum at (32μg/mLis 7.67 ±0.05) while minimum (2μg/mL is -1545.4 ±0.05.). In antifungal activity tested against two different pathogen and shows the zone inhibition respectively Candida albicans (12.8mm) Aspergillus niger (14.4mm) while For Antibacterial activity used three bacterial sustain shows inhibition zone respectively Staphylococcus aureus (12mm), Bacillus subtilis (10mm), P. mirabilis (12.8mm) and E.coli (13mm). On overall analysis come to say that brown algae are greatest potential of nutrition of human health while pharmacological analysis is useful the therapeutic application